Legal Analysis of the Implementation of the ITE Law in Combating Cybercrime in Indonesia - Annie Myranika; Felina Young (The International Journal of Law Review and State Administration, 2025)
This article examines the implementation of Indonesia’s Electronic Information and Transactions Law (UU ITE) in combating cybercrime through a juridical analysis approach. The rapid development of digital technology has created various forms of cyber offenses such as data theft, online fraud, hacking, and the dissemination of unlawful content, which require adequate legal regulation. This study analyzes the normative aspects of UU ITE, the effectiveness of its enforcement, and the main challenges faced in law enforcement, including limited technological capacity, interpretative ambiguities of several articles, and institutional constraints. The findings indicate that although UU ITE has provided an essential legal framework for addressing cybercrime, its implementation remains constrained by technological development gaps, regulatory limitations, and the need for continuous legal reform. Therefore, strengthening legal frameworks, enhancing law enforcement capacity, and promoting inter-agency cooperation are necessary to improve the effectiveness of cybercrime prevention and enforcement in Indonesia.